A crioterapia reduz a espasticidade muscular, mas não altera o senso de posição articular e a velocidade da marcha em pacientes crônicos pós-AVC : um ensaio clínico crossover randomizado e controlado - Garcia, Luccas Cavalcanti (2017)
Background: Spasticity is a neuromuscular disorder that causes functional impairments in post-stroke individuals. Cryotherapy is used to temporarily reduce spasticity, but its effects on sensorimotor control components, such as the joint position sense (JPS), and gait performance in hemiparetics individuals are still unclear. Objectives: To evaluate the immediate effects of cryotherapy (ice pack modality) on the spasticity level, ankle JPS and gait performance in chronic hemiparetic individuals post-stroke. Methods: Sham-controlled crossover design. Sixteen chronic hemiparetic subjects were randomized into two groups: 1) those who received cryotherapy and after fifteen days they received control intervention (Cryotherapy Group – CT); and 2) those who received control intervention and after fifteen days they received cryotherapy (Control Intervention Group – CI). Joint position sense (JPS) of the ankle was measured in the paretic side by using a Biodex Multi-joint System 3 dynamometer before and after receiving 20 minutes of either applications. The lower absolute error scores were calculated for data analyses and used to determine proprioception. The spasticity levels of ankle’s muscles were scored according to the Modified Ashworth Scale. The 6-meter walking test was applied to determine participants walking speed. Results: Cryotherapy reduced the spasticity level of ankle dorsiflexors and plantar flexor muscles, without altering the ankle joint position sense and gait speed. Conclusion: Cryotherapy (ice pack) reduced spasticity level in chronic hemiparetic patients, without altering the ankle JPS and gait performance.